The end-of-life needs of Aboriginal and immigrant communities: a challenge to conventional medical models - Rosemary Leonard; Joy Paton; Peta Hinton; Sally Greenaway; Jody Thomson (Frontiers Media S.A., 2023)
IntroductionConcerns have been raised internationally about the palliative care needs of migrants and First Nations people. This article presents insights from research investigating the end-of-life needs of Aboriginal and culturally and linguistically diverse people living in Western Sydney, Australia. This region has a large rapidly growing, and highly diverse population and on average low socioeconomic status. The research was guided by an advisory panel made up of representatives of supportive and palliative medicine, bereavement support, Aboriginal health, and multicultural health facilities. It aimed to generate findings to support the delivery of culturally sensitive services in the public health system.MethodThe multi-method design and the conduct of the research were informed by the literature on researching with marginalized groups which highlights the ethical considerations needed to avoid replicating past injustices. Qualitative data was generated from key informants and community focus groups.ResultsThe analysis revealed seven themes and some suggested solutions which were relevant across several themes. The seven themes were: the Need for trusted relationships; Talking about death and dying; Knowledge of key services; Decision-making and obtaining consent from the patient; Appropriate physical spaces; Cultural practices around EOL; and Language barriers.DiscussionWithin each theme a variety of cultural beliefs and practices were revealed that conflicted with mainstream medical systems, indicating the need for changes in such systems. 'Compassionate Communities' was identified as a model to support the necessary changes.